Receptor-mediated gene delivery by folic acid-modified stearic acid-grafted chitosan micelles - Du Y (Dove Medical Press, 2011)
Yong-Zhong Du1, Li-Li Cai1, Jin Li1, Meng-Dan Zhao2, Feng-Ying Chen2, Hong Yuan1, Fu-Qiang Hu11College of Pharmaceutical Sciences, 2Women’s Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of ChinaBackground: Cationic polymers have been accepted as effective nonviral vectors for gene delivery with low immunogenicity unlike viral vectors. However, the lack of organ or cell specificity sometimes hampers their application and the modification of polymeric vectors has also shown successful improvements in achieving cell-specific targeting delivery and in promoting intracellular gene transfer efficiency.Methods: A folic acid-conjugated stearic acid-grafted chitosan (FA-CS-SA) micelle, synthesized by a 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide-coupling reaction, was designed for specific receptor-mediated gene delivery.Results: Due to the cationic properties of chitosan, the micelles could compact the plasmid DNA (pDNA) to form micelle/pDNA complexes nanoparticles. The particle size and zeta potential of the FA-CS-SA/pDNA complexes with different N/P ratios were 100–200 nm and −20 to −10 mV, respectively. The DNase I protection assay indicated that the complexes can efficiently protect condensed DNA from enzymatic degradation by DNase I. A cytotoxicity study indicated that the micelles exhibited less toxicity in comparison with LipofectamineTM 2000. Using SKOV3 and A549 as model tumor cells, the cellular uptake of micelles was investigated.Conclusion: It was found that cellular uptake of FA-CS-SA in SKOV3 cells with higher folate receptor expression was faster than that in A549 cells with a short incubation time. Luciferase assay and green fluorescent protein detection were used to confirm that FA-CS-SA could be an effective gene vector. Transfection efficiency of the FA-CS-SA/pDNA complexes in SKOV3 cells was enhanced up to 2.3-fold compared with that of the CS-SA/pDNA complexes. However, there was no significant difference between the transfection efficiencies of the two complexes in A549 cells. Importantly, the transfection efficiency of FA-CS-SA/pDNA decreased with free FA pretreatment in SKOV3 cells. It was concluded that the increase in transfection efficiency of the FA-CS-SA/pDNA complexes was attributed to folate receptor-mediated endocytosis.Keywords: stearic acid-grafted chitosan, folic acid, polymeric micelles, folate receptor targeting, gene delivery